Varying magnesium concentration elicits changes in inflammatory response in human umbilical vein endothelial cells (HUVECs) - Almousa, Lujain A.; Salter, Andrew M.; Langley-Evans, Simon C. (John Libbey Eurotext, 2018)
The aims of this study were to determine whether low concentrations of magnesium in vitro exacerbated the human umbilical vein endothelial cell (HUVEC) response to inflammatory challenge, and whether expression of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) through the toll-like receptor 4 (TLR4) played a role in this process. HUVECs were incubated with different concentrations of Mg (low- 0.1mM, control- 1mM, high- 5mM) for 72 h before being stimulated with bacterial lipopolysaccharide (LPS) for 4 h. The response of cells to LPS was greater in cells cultured in low Mg, relative to control cells and suppressed in high Mg. Expression of NF-κB was increased in low-Mg and decreased with high Mg. Low Mg increased the expression of TLR4 mRNA, but only in the presence of LPS. Antibody blockade of TLR4 but not TLR2 blunted the response of cells to LPS in low Mg, such that they were similar to unblocked 1mM Mg cells. Associations of Mg with cardiovascular disease may therefore relate to inflammatory responses mediated through the TLR4/NF-κB pathway.